2018
DOI: 10.1161/circulationaha.118.034456
|View full text |Cite
|
Sign up to set email alerts
|

Newer-Generation Ultrathin Strut Drug-Eluting Stents Versus Older Second-Generation Thicker Strut Drug-Eluting Stents for Coronary Artery Disease

Abstract: -Contemporary second-generation drug-eluting stents (DES) have superior efficacy and safety compared with early generation stents in patients undergoing percutaneous coronary intervention (PCI), in part related to their thinner struts. Whether newer generation ultra-thin DES further improve clinical outcomes compared with older second-generation thicker strut DES is unknown. -We searched PUBMED, EMBASE, and CENTRAL for randomized clinical trials that compared newer generation ultra-thin strut DES (defined as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 27 publications
10
134
0
2
Order By: Relevance
“…Ultrathin strut drug-eluting stents have been associated with a lower risk of target lesion failure and myocardial infarction compared with thin strut drug-eluting stents in a meta-analysis of randomised trials. 23 A reduction in strut thickness has been shown to mitigate inflammation, vessel injury, neointimal proliferation, and thrombus formation. 11,24,25 These findings are particularly relevant in the inflammatory milieu of acute STEMI and might explain the differences we observed in the incidence of target lesion failure and target lesion revascularisation in patients treated with biodegradable polymer sirolimus-eluting stents compared with those treated with durable polymer everolimus-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrathin strut drug-eluting stents have been associated with a lower risk of target lesion failure and myocardial infarction compared with thin strut drug-eluting stents in a meta-analysis of randomised trials. 23 A reduction in strut thickness has been shown to mitigate inflammation, vessel injury, neointimal proliferation, and thrombus formation. 11,24,25 These findings are particularly relevant in the inflammatory milieu of acute STEMI and might explain the differences we observed in the incidence of target lesion failure and target lesion revascularisation in patients treated with biodegradable polymer sirolimus-eluting stents compared with those treated with durable polymer everolimus-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…The study results have to be seen in the context of the evolution of stent technology, in particular in decreasing strut thickness. A recent meta‐analysis has shown that ultra‐thin strut DES (<70 μm) are associated with lower target‐lesion failure rates . It can be speculated that an anti CD‐34 antibody layer on an ultra‐thin strut DES could result in even faster endothelial strut coverage.…”
Section: Discussionmentioning
confidence: 99%
“…This likely explains the association of lower risk of ST with TAT which has a longer duration of DAPT. Nevertheless, stent technology that has advanced over the years with thinner stent struts and new bioresorbable polymers that further reduce the prothrombotic milieu is more likely a contributing factor in our results and majority of included studies in our analysis utilized DES . However, such benefit was not observed in our analysis of RCTs.…”
Section: Discussionmentioning
confidence: 88%